Remediation by enhanced natural attenuation; an environment-friendly remediation approach - Ayilara, Modupe S.; Adeleke, Bartholomew S.; Adebajo, Mosimininuoluwa T.; Akinola, Saheed A.; Fayose, Chris A.; Adeyemi, Uswat T.; Gbadegesin, Lanre A.; Omole, Richard K.; Johnson, Remilekun M.; Edhemuino, Mary; Ogundolie, Frank Abimbola; Babalola, Olubukola O. (Frontiers in Environmental Science, 2023)
The uncontrolled use of chemicals, urban wastes, nuclear resources, mining, petrochemicals and disposal of sewage sludge only a few anthropogenic activities that have contributed to the rapid industrialization and severe heavy metal contamination of soils and waterways. Both inorganic and organic pollutants, such as heavy metals, pesticides, petroleum hydrocarbons, and polycyclic aromatic hydrocarbons, can impact the composition and functionality of soils. Soils and plants are affected by pollution, thus, pose a dire threat to food security. This directly renders the soil unuseful for agricultural purposes, destroys the beneficial microbes in the soil, reduces the soil organic matter content, causes the imbalance of soil nutrients, affects plant growth and the interaction between the plants and microbes, subsequently affecting the soil and crop productivity. In addition, environmental pollutants affect human health, leading to different illnesses such as headaches, allergies, coughs, depression, chest pain, nausea, diabetes, liver problems, cancers, eye problems, and so on. Remediation (physical, chemical or biological) is therefore necessary to reduce the impacts of these pollutants in the environment. Bioremediations involve using natural products from plants, microbes, and so on, to detoxify the environment and make it useful or productive again. A key type of remediation is the Remediation by Enhanced Natural Attenuation (RENA) which involves the turning of soil to promote microbial proliferation, aeration, nutrient availability, moisture and consequently, the degradation of pollutants. This review discusses the technology of RENA, the associated microbes, the mechanism of its action, challenges associated with its usage and recommendations to advance the use of RENA for a sustainable environment.